2012
DOI: 10.1007/s12032-012-0352-3
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative lymphocyte count is a favorable prognostic factor of disease-free survival in non-small-cell lung cancer

Abstract: Recently, the prognostic value of cancer-related inflammatory response has been revealed. Previous studies showed that peripheral neutrophils and lymphocytes had significant impact on the prognosis of advanced and early-node-negative non-small-cell lung cancer (NSCLC). The purpose of this study was to investigate the prognostic value of preoperative lymphocyte and neutrophil counts in patients with NSCLC who underwent lobectomy and lymph node dissection and adjuvant chemotherapy. Retrospective analyses were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 35 publications
4
59
1
1
Order By: Relevance
“…Also, low lymphocyte count was related with lymphatic invasion and recurrence of NSCLC. In contrast, peripheral neutrophil count had no impact on survival (Zhang et al, 2013).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Also, low lymphocyte count was related with lymphatic invasion and recurrence of NSCLC. In contrast, peripheral neutrophil count had no impact on survival (Zhang et al, 2013).…”
Section: Discussionmentioning
confidence: 78%
“…Also low lymphocyte count was correlated with vascular invasion and recurrence of NSCLC (Kobayashi et al, 2012). Similarly Zhang et al (2013) reported that lowlymphocyte count was an independent unfavorable prognostic factor of disease-free survival in patients with NSCLC. Also, low lymphocyte count was related with lymphatic invasion and recurrence of NSCLC.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, fibrinogen may protect tumor cells from natural killer cytotoxicity (28). Conversely, lymphocytes suppress tumor growth and invasion through their cytolytic activity (29). Increased NLR may represent increased neutrophil counts, decreased lymphocyte counts, or both.…”
Section: Discussionmentioning
confidence: 99%
“…It may be associated lymphopenia or increasing numbers of neutrophils and monocytes (Donnem et al, 2010). Lymphocytes play a critical role in cell mediated antitumor immune response in various cancers (Halazun et al, 2008; CD8(+) T cells can control tumor growth by cytotoxic activity and inducing apoptosis of tumor cells (Leitch et al, 2007;Schmidt et al, 2007;Zhang et al, 2013). In the other hand neutrophilia often accompanies the diagnosis of cancer.…”
Section: Discussionmentioning
confidence: 99%